New challenges for information professionals in the present information technology era / Azmi Salim - Salim, Azmi (Universiti Teknologi MARA Cawangan Pahang, 2000)
The advancement of today's world, requires the society around the globe to race against the fast changing technology that affects every single part of our daily life. From Offices to stores, from markets to homes. According to Tan Sri Dr. Othman Yeop Abdullah, Executive Chairman of "Perbadanan Pembangunan Multimedia", the number of internet users in Malaysia is expected to have a rise to 6 or 7 million users by the end of year 2000. This shows that in Malaysia alone the trend towards technology happens so fast. Those who are not able to follow the trend will certainly be left behind and of course the challenges of the 21 st Century would be bitter to them. Information Professionals have no exception. 6 major areas of challenge ranging from conceptual development, automation, education and training, social awareness, user education and professionalism are highlighted throughout this writing.